2020
DOI: 10.5336/nurses.2020-73591
|View full text |Cite
|
Sign up to set email alerts
|

Medication That Springs from Our Soul: 'Compassion' Can it be Taught

Abstract: The word mercy is stated to be derived from the words "pity, affection". 3 According to the definition of Turkish Language Institution (TDK), compassion is "the sadness and pity that one feels in the face of the unfavorable conditions that a person or another living thing experiences". 4 According to the Oxford English Dictionary, on the other hand, the word "compassion" originates from the Latin word "compati", which means "suffering". 2 The meaning and definition of compassion, how it can be measured, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…31,32 There is a consensus about the fact that compassion is teachable. 9 Jazaeri et al reported that a group receiving compassion training had an increased level of compassion at the end of the training, which also had positive effects on psychology and well-being. 33 Despite all these positive opinions, Schulz et al stated that compassion plays a role in establishing a good relationship between the caregiver and the care receivers, however, a high level of compassion may have disadvantages for the caregiver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 There is a consensus about the fact that compassion is teachable. 9 Jazaeri et al reported that a group receiving compassion training had an increased level of compassion at the end of the training, which also had positive effects on psychology and well-being. 33 Despite all these positive opinions, Schulz et al stated that compassion plays a role in establishing a good relationship between the caregiver and the care receivers, however, a high level of compassion may have disadvantages for the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…Compassion Scale (CS) was developed by Pommier and the validity and reliability analysis of the Turkish version was performed by Akdeniz and Deniz. 14,15 It contains 24 items presented in a 5-point Likert scale format and has six sub-scales including kindness (6,8,16,24), indifference (2,12,14,18), common humanity (11,15,17,20), separation (3,5,10,22), mindfulness (4,9,13,21) and disengagement (1,7,19,23). Items in the indifference, separation and disengagement subscales are reverse-coded.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation